2020
DOI: 10.1007/s00213-020-05715-5
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of Olanzapine plasma concentrations in monitoring treatment efficacy and metabolic disturbances in first-episode psychosis

Abstract: IntroductionThe role of Olanzapine therapeutic drug monitoring is controversial. The present study explores the associations of Olanzapine plasma concentrations with clinical response and metabolic side effects in first episode psychosis (FEP) after 2 months of treatment. MethodsForty-seven patients were included. Improvement in clinical symptomatology was assessed using the PANSS. Metabolic assessment included weight, blood pressure, waist circumference, blood glucose,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…It is difficult to compare this association with previous findings due to differences in follow‐up duration or sample of patients. For example, a previous study of first‐episode olanzapine‐treated patients suggested a threshold of 23.28 ng/ml for CRW (>7%) after 2 months of olanzapine treatment 50 . A potential explanation for the gap between this threshold and the threshold adopted by us (80 ng/ml) may be the fact that our patients were not first‐episode patients and thus not antipsychotic exposure‐free.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is difficult to compare this association with previous findings due to differences in follow‐up duration or sample of patients. For example, a previous study of first‐episode olanzapine‐treated patients suggested a threshold of 23.28 ng/ml for CRW (>7%) after 2 months of olanzapine treatment 50 . A potential explanation for the gap between this threshold and the threshold adopted by us (80 ng/ml) may be the fact that our patients were not first‐episode patients and thus not antipsychotic exposure‐free.…”
Section: Discussionmentioning
confidence: 59%
“…For example, a previous study of first‐episode olanzapine‐treated patients suggested a threshold of 23.28 ng/ml for CRW (>7%) after 2 months of olanzapine treatment. 50 A potential explanation for the gap between this threshold and the threshold adopted by us (80 ng/ml) may be the fact that our patients were not first‐episode patients and thus not antipsychotic exposure‐free. Additionally, a study of chronic patients titrated up to 20 mg/day olanzapine reported a threshold for dose‐weighted plasma levels of 20.6 ng/ml for CRW after 6 weeks, 51 which is a shorter follow‐up window compared to ours.…”
Section: Discussionmentioning
confidence: 71%
“…The present manuscript had the objective to study the relationship between plasma concentrations of LAI atypical antipsychotics and clinical effectiveness as measured by direct (clinical) and indirect (experimental) parameters. This topic can have clinical utility to predict treatment response and prognosis of patients affected by severe mental disorders (e.g., SCZ) and treated with LAI SGAs [43].…”
Section: Discussionmentioning
confidence: 99%
“…The intra- and inter-day precision and relative errors were <15%. The olanzapine concentration–dose (C/D) ratio is a potential predictor of the effectiveness of the drug in patients with schizophrenia [ 19 ]. Therefore, we further investigated the relationship between the olanzapine C/D ratio and the polymorphisms of metabolizing enzymes.…”
Section: Methodsmentioning
confidence: 99%